Inflammasome-Regulated Pyroptotic Cell Death in Disruption of the Gut-Brain Axis After Stroke - Kerr, Nadine A.; Sanchez, Juliana; O’Connor, Gregory; Watson, Brant D.; Daunert, Sylvia; Bramlett, Helen M.; Dietrich, W. Dalton (Translational stroke research, 2022)
Approximately 50% of stroke survivors experience gastrointestinal complications. The innate immune response plays a role in changes to the gut-brain axis after stroke. The purpose of this study is to examine the importance of inflammasome-mediated pyroptosis in disruption of the gut-brain axis after experimental stroke. B6129 mice were subjected to a closed-head photothrombotic stroke. We examined the time course of inflammasome protein expression in brain and intestinal lysate using western blot analysis at 1-, 3-, and 7-days post-injury for caspase-1, interleukin-1β, nod-like receptor protein 3 (NLRP3), and apoptosis speck-like protein containing a caspase-recruiting domain (ASC) and gasdermin-D (GSDMD) cleavage. In a separate group of mice, we processed brain tissue 24 and 72 h after thrombotic stroke for immunohistochemical analysis of neuronal and endothelial cell pyroptosis. We examined intestinal tissue for morphological changes and pyroptosis of macrophages. We performed behavioral tests and assessed gut permeability changes to confirm functional changes after stroke. Our data show that thrombotic stroke induces inflammasome activation in the brain and intestinal tissue up to 7-day post-injury as well as pyroptosis of neurons, cerebral endothelial cells, and intestinal macrophages. We found that thrombotic stroke leads to neurocognitive and motor function deficits as well as increased gut permeability. Finally, the adoptive transfer of serum-derived EVs from stroke mice into naive induced inflammasome activation in intestinal tissues. Taken together, these results provide novel information regarding possible mechanisms underlying gut complications after stroke and the identification of new therapeutic targets for reducing the widespread consequences of ischemic brain injury.